Analisis Kinerja dan Kualitas Pelayanan Angkutan Umum Kota Ambon (Rute Laha-Ambon) - Tentua, Afiano; Metekhoy, Ir. Juliet G; Wangean, Febrino (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2026)
This study is titled "Performance and Quality Analysis of Public Transportation Services in Ambon City (Laha-Ambon Route)", aiming to evaluate the performance and service quality of public transportation on the Laha-Ambon route and analyze the relationship between technical performance and service quality based on user perceptions. The research employs a quantitative descriptive approach with primary data collected through dynamic surveys, static surveys, and interviews with 100 users. Service performance is measured using seven main indicators according to the Directorate General of Land Transportation standards: load factor, frequency, fleet availability, travel speed, headway, service time, and travel time. Service quality is analyzed using the Importance Performance Analysis (IPA) method based on 20 attributes covering comfort, accessibility, reliability, and safety. The results indicate that the performance of the public transportation service on the Laha route falls into the "moderate" category with a total score of 12, while the quality of service from users’ perceptions is considered "good" with a suitability level of 67.01%. Correlation analysis shows a strong positive relationship between technical performance and service quality (r=0.653; p < 0.05). Although some technical indicators are not yet optimal, user satisfaction remains high due to directly experienced service factors such as ease of boarding and alighting, security, and polite driver behavior. The study recommends improvements on the less optimal performance indicators, adjustments of operational standards to be more adaptive to user needs, and continuous communication enhancement with users to improve service quality.